Trends in Hi-Tech Examination Malpractices: Lessons from Nigeria (2019)
Information and communication technologies (ICTs) have revolutionized every sphere of human endeavor including education. However, the use of ICTs in Education is not without challenges. One of the major challenges of ICTs in education is examination malpractice. Educational assessment and evaluation are the means through which the attainment of educational objectives is validated. Examination malpractice is considered as a huge challenge to these processes. This paper focuses on the trends and threats of hi-tech examination malpractice in the Nigerian educational system. It discusses the factors that precipitate examination malpractices and implications on the attainment of educational objectives. The paper identified proliferation of mobile phones and other private digital assistants (PDAs) as a major driving factor for e-cheating. It further outlined corruption, poor funding, legal and moral issues as challenges militating against efforts to end the ugly trend. It concludes that the co-operation of Government, parents, school administrators, examination bodies and security agencies is required to chart a way forward.